Electrochemical Performance of NiCo2O4 Spinel Cathodes for Intermediate Temperature Solid Oxide Fuel Cells. Issue 1 (7th November 2021) - Thaheem, Imdadullah; Ali, Shamshad; Waqas, Muhammad; Hussain, Ayaz; Soomro, Afaque Manzoor; Bhutto, Zuhaibuddin; Shah, Syed Ali Raza; Muhammad, Wazir; Shah, Jalal
Abstract : It is a great challenge to develop the highly efficient cathode material for solid oxide fuel cells (SOFCs) at intermediate temperature, while high electronic conductivity, good thermal and chemical compatibility, and superior electrochemical performance of the AB2 O4 ‐type spinel is attractive electrode material. Herein, the NiCo2 O4 spinel is developed using the glycine‐nitrate process (GNP) method as a cathode material for IT SOFCs. The characterization of the phase structure, microstructure, and electrochemical performance are done using X‐ray diffraction, scanning electronic microscopy, and electrochemical impedance spectroscopy. The results show that NiCo2 O4 exhibited a single cubic structure and good chemical compatibility with a ((Sc2 O3 )0.1(CeO2 )0.01(ZrO2 )0.89) (ScCeSZ) electrolyte material at 900 °C for 10 h. Furthermore, a NiO–YSZ anode |NiO–YSZ, AFL | ScCeSZ |NiCo2 O4 SOFC cell exhibits the maximum power density (MDP) of 0.73 and 1.04 W cm −2 at 750 and 800 °C, respectively. These results recommend the spinel‐structured NiCo2 O4 is a potential cathode material for IT SOFC application. Abstract : Over the past three decades, cobaltite‐based perovskite materials, such as La0.6 Sr0.4 Co0.2 Fe0.8 O3‐δ, Ba0.5 Sr0.5 Co0.8 Fe0.2 O3‐δ, and PrBaCo2 O5+δ, have been intensively studied due to their superior mixed ionic and electronic conductivities, and promising oxygen reduction reaction (ORR) catalytic activities in intermediate temperature (IT ranges. Herein, NiCo2 O4 spinel using glycine‐nitrate process (GNP) method as a cathode material for IT SOFCs is developed.